Turkish Standardization of Wechsler Adult Intelligence Scale- Revised (WAIS-R): Pilot Study - Nilhan SEZGİN; Gülbahar BAŞTUĞ; Sibel YARGICI KARAAĞAÇ; Banu YILMAZ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
The aim of this study was to gather data for the pilot study of Wechsler Adult Intelligence Scale-Revised (WAIS-R). The Turkish translation of WAIS-R was individually administered to 134 adults (67 males, 67 females), from three socioeconomic groups (SES) between ages 16-70. The results of the statistical analysis showed that there were modifications in the item difficulties of the Information, Picture Completion, Comprehension, Picture Arrangement, Vocabulary and Block Design sub-scales. The results of the analysis of variance indicated that the main effect of SES and age were statistically significant on most of the sub-scales. On the other hand the main effect of sex was statistically significant on the sum of raw scores of Information and Arithmetic sub-scales, in favor of males. Moreover the interaction effect of age and SES was significant only on the raw score of the Digit Symbol sub-scale. No other interaction effect was significant on other sub-scales. The Spearman-Brown, Cronbach Alpha coefficients and inter- correlations calculated were very high and significant, indicating that the internal consistency of the Turkish WAIS-R is high. The suggestions for the future standardisation study were discussed in the light of the findings of this pilot study.